Naturopathic community clinics: an international cross-sectional survey - Iva Lloyd; Sophia Gerontakos; Valentina Cardozo (BMC, 2021)
Abstract Background Globally, naturopathic practitioners offer services in 98 countries, reaching every world region and providing care to diverse populations for a range of acute and chronic health conditions. Community clinics provide free or low-cost healthcare services and play a key role in providing necessary primary healthcare for underprivileged or marginalized populations. However, the reach and impact of naturopathic community clinics (NCCs) has not yet been examined. The aim of this study was to identify the characteristics of NCCs around the world, determine the types of services they offer and provide insight into the populations being served. Methods Two online cross-sectional surveys were administered using purposive and snowball sampling. A 6-item screening survey was administered first to identify clinics and institutions who fit the criteria for NCC services, followed by a 40-item follow-up survey. Descriptive analysis was conducted using frequencies and means. Results The screening survey returned a total of 37 responses from six world regions. Of those respondents who indicated involvement in NCCs, 74% went on to complete the follow-up survey. The majority of the responding NCCs were located in North America (50%), followed by Western Pacific (17%), Europe (10%), Asia (13%), Latin America (7%) and Africa (3%). The vast majority (71%) of the NCCs that have been in operation for more than 10 years are located in North America, while 43% of the NCCs that have been operational less than 5 years are in the Western Pacific Region. 80% of the responding NCCs were affiliated with a naturopathic school. The majority of respondents (76%) mentioned that they aim to serve underserved and/or marginalized populations, with 34% indicating that their target population is low-income families, 21% focusing on serving immigrants and refugees, 21% on serving people experiencing homelessness, 14% on serving Indigenous peoples, 14% on serving those with specific gender differences, 10% on serving seniors and 10% on serving drug users. Conclusion The naturopathic profession offers free or significantly low-cost naturopathic services through community clinics around the world. The findings of this survey provide insight into the important role of the naturopathic profession in primary health care and provide rationale for exploring this topic in greater detail.